FRI0333 Lesinurad, a Selective Uric Acid Reabsorption Inhibitor, in Combination with Allopurinol: Results from a Phase III Study in Gout Patients Having an Inadequate Response to Standard of Care (Clear 2). (9th June 2015) - Bardin, T.; Keenan, R.; Khanna, P.; Kopicko, J.; Fung, M.; Bhakta, N.; Adler, S.; Storgard, C.; Baumgartner, S.; So, A.
Abstract : Background: Lesinurad (RDEA594) is a selective uric acid reabsorption inhibitor (SURI) being investigated for treatment of gout in combination with xanthine oxidase inhibitors. Objectives: Assess efficacy and safety of lesinurad in combination with allopurinol (ALLO) in gout patients with inadequate response to standard of care (SOC) ALLO dosing (NCT01493531 ). Methods: CLEAR 2 was a 12-month, randomized, double-blind, global phase III trial to evaluate lesinurad (200 mg or 400 mg oral, qd) in combination with ALLO vs ALLO+placebo (PBO). Patients were ages 18-85 yrs on stable, medically appropriate SOC ALLO doses ≥300 mg (≥200 mg in moderate renal impairment), as determined by investigator, with serum uric acid (sUA) ≥6.5 mg/dL at screening and ≥2 gout flares in prior 12 months. Primary endpoint was proportion of patients meeting sUA target of <6.0 mg/dL (<360 μmol/L) by Month 6. Secondary endpoints included mean gout flare rate requiring treatment (GFRT; Month 6 through 12) and proportion of patients with complete resolution of ≥1 target tophus by Month 12. Safety assessments included treatment-emergent AEs and laboratory data. Results: Patients (N=610) were mostly male (96.2%), mean ± SD age was 51.2±10.9 yrs, and duration since gout diagnosis was 11.5±9.3 yrs. Most patients (84.1%) received ALLO 300 mg (range: 200-900 mg) daily; 23.6% had tophi at screening (measurable target tophi at baseline, 15.9%) and baseline sUA was 6.90±1.19 mg/dL. Lesinurad at both doses in combination with ALLO significantly increased proportions of patients achieving sUA targets (<6.0 mg/dL and <5.0 mg/dL) vs ALLO+PBO at all visits, with more than twice as many patients achieving targets at Month 6 (Figure ). No significant differences were observed between groups in mean rate of GFRT (Month 6 to 12) or patients with complete target tophus resolution (by Month 12). Safety data are reported in the Table. Serum creatinine (sCr) elevations were observed, resolving in most cases without interrupting study medication. Conclusions: Lesinurad (200 or 400 mg) in combination with ALLO significantly increased the proportion of patients achieving sUA target at 6 months, with more than twice as many patients reaching goal of <6.0 mg/dL vs ALLO+PBO. Lesinurad was generally well tolerated at lower dose, where AE profile was comparable to ALLO alone and 2.0x sCr elevations were reversible. Combination therapy with lesinurad and ALLO represents a potentially promising treatment option for gout patients who are inadequately controlled on ALLO. Acknowledgements: Research sponsored by Ardea Biosciences/AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: T. Bardin Grant/research support from: Ipsen, Menarini, Consultant for: AstraZeneca, Ipsen, Menarini, Novartis, Savient, Sobi, Takeda, R. Keenan Consultant for: AstraZeneca, Crealta Pharmaceuticals, Takeda, P. Khanna Speakers bureau: Takeda, J. Kopicko Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., M. Fung Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., N. Bhakta Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., S. Adler Employee of: AstraZeneca Pharmaceuticals, C. Storgard Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., S. Baumgartner Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., A. So Consultant for: Novartis, AstraZeneca, Menarini